PENGARUH PERILAKU KONSUMEN DAN KELOMPOK REFERENSI SERTA BENTUKAN BRAND IMAGE PADA INDUSTRI PERBANKAN - Alvi Furwanti Alwie (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2006)
The research is conducted at main branch office of PT Bank Riau and aims to investigate the consumer behavior in banking industry, to look for refference group, which has influens on bangking consumer behavourial activity and to investigate what kind of attributes, those are influential in forming the branch image at main branch office of PT bank Riau